Pathway, classification and removal efficiency of microplastics in wastewater treatment plants. (December 2019) - Ngo, Phuong Linh; Pramanik, Biplob Kumar; Shah, Kalpit; Roychand, Rajeev
Abstract: Microplastics (MPs) contamination in water environment has recently been documented as an emerging environmental threat due to their negative impact on the ecosystem. Their sources are many, but all of them are from synthetic materials. The sources of MPs are cosmetics and personal care products, breakdown or abrasion processes of other plastic products, textile and tyre, bitumen and road marking paints. Because of their low density and small particle size, they are easily discharged into the wastewater drainage systems. Therefore, the municipal wastewater treatment plants (WWTPs) are indicated to be the main recipients of MPs before getting discharged into the natural waterbodies. Therefore, understanding the occurrence and fate of MPs in WWTPs are of great importance towards its control. The aim of this article is to provide a comprehensive review to better understand the pathways of MPs before entering the WWTPs, characteristics of MPs in wastewater, and the removal efficiency of MPs of the existing wastewater treatment technologies adopted by the WWTPs. This review also covers the development of potential microplastics treatment technologies investigated to date. Based on the review of existing literature, it is found that the existing WWTPs are inefficient to completely remove the MPs and there is a risk that they may get discharged into the ambient water sources. Graphical abstract: Image 1 Highlights: Polyester is one of major MP components in the WWTPs. Existing wastewater treatment plants cannot completely remove microplastics. Photocatalysis based technology to destruct MPs is needed.